Progress of competitions in informatics: A success story - Jovanov, Mile; Stankov, Emil; Kostadinov, Bojan; Ackovska, Nevena (FCSE, 2012)
Competitions in informatics are a perfect opportunity to introduce to pupils the art of programming and create a very solid background for becoming engineers in informatics. The Computer Society of Macedonia, as the main organizer of the Macedonian national competitions in informatics, through the last few years has made an effort to increase the quality of the competitions in order to achieve better results in the international competitions. In this paper we present the format of the international competitions and the results of Macedonian contestants at international level. More importantly, the history of competitions held in Macedonia is presented in order to explain the way to the success of Macedonian teams.